Menuju Beragama Secara Swalayan - Yusdani Yusdani (Unisia, 2007)
The article investigates Islam as revealed religion, because it originates from Allah. The problem is that when Islam is interpreted by Moslems, the pluralism of Islam, including in Indonesia, emerges. This pluralism is caused by the influence of various factors, such as sociological, cultural, and intellectual ones. This can be called as the aesthetics of recep- tion, and Islam itself denotes as poly-interpretable religion. Departing from such pluralism in understanding Islam, Indonesian Moslems should develop the tolerant attitude, not only among Moslems, but also between them and the followers of other religions. Keywords: Islam, revealed religion, pluralism, aesthetic reception, tolerant.